Pengenalan Virtual Laboratory Berbasis Physics Education Technology (PhET) Simulation sebagai Alternatif Praktikum pada Siswa Kelas VII SMPN 26 Makassar - Andi Umdatul Hasanah; Eka Nurul Sakinah; Adinda Aulia Pratama Putri; Gusti Yulianda; Sitti Rahma Yunus (JKM: Jurnal Kemitraan Masyarakat, 2024)
The development of education and technology in the era of globalization continues to require new products and innovations. This community service activity was carried out by introducing PhET Interactive Simulation Virtual laboratory as an alternative practicum activity at SMPN 26 Makassar with 55 participants. The purpose of this community service program is to improve students' understanding of physics concepts through practical activities using PhET. The results show that PhET Simulation is quite effective if used as a learning media in Junior High School. The use of PhET interactive Simulation can be an alternative physics learning process to increase student enthusiasm for learning so that it can improve student competence in understanding science concepts.